The Possibility Of Using Fair Value Accounting To Improve The Quality Of Accounting Information In Egyptian Banks - An Applied Study - Elgabali, Walid (جامعة الوادي - University of Eloued, 2020)
The study aims to achieve recognition of fair value Accounting and good Financial reports for Egyptian banks listed on the Egyptian Stock Exchange and knowledge of the impact of fair value accounting on the suitability and reliability of financial reporting information. The study reached a set of results, the most important of There is a positive relationship between fair value accounting and the reliability of financial reporting information to Egyptian banks listed in the Egyptian market for securities, Through the study could adopt Egyptian banks fair value accounting , Complex financial reporting information in accordance with the fair value accounting have strong indications about future forecasts and Info financial reports prepared according to the fair value of a positive influence in decision making.
مقال
Keywords: fair value ; accounting information